Penerapan Aplikasi Manten-Ku untuk Optimalisasi Layanan pada Khalisa Muslim Wedding Banjarnegara - Ferry Febrianto; Khalimaturofi'ah Khalimaturofi'ah (LPPM STT Terpadu Nurul Fikri, 2026)
Khalisa Muslim Wedding Banjarnegara is a service business that offers wedding packages, bridal makeup, pre-wedding services, graduation services, and clothing rentals. Currently, the ordering process is still done conventionally, with customers having to come directly to the office to order packages. Customer data is still recorded on paper and summarised in a ledger. This often causes various problems, such as lost, damaged, or difficult-to-find data. The promotion process is still limited to telephone and social media such as Instagram. Customers see photos without getting detailed information about the contents and prices of available wedding packages. This study aims to develop a website-based wedding package booking application to facilitate the booking process and manage customer data. The methods used include data collection and the Waterfall system development. The application was designed using Flowchart, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD) modeling tools, and implemented using PHP and the MySQL database. Black Box testing results showed a 94% success rate, indicating that all system functions were running according to requirements. Meanwhile, the results of User Acceptance Testing (UAT), with an average score of 69.28%, indicate that the application is acceptable to users and considered helpful for ordering, promotion, and data processing.